Effect of HfO2 nitridation on structural, optical and electrical properties of GaN films grown on HfO2/Si(100) by laser molecular beam epitaxy. (3rd August 2018) - Ramesh, Ch; Tyagi, P; Singh, P; Kumar, A; Senthil Kumar, M; Kushvaha, S S
Abstract: Growth of high quality III-nitride films on high-k oxide/Si substrates is crucial for the fabrication of nitride based metal-oxide-semiconductor devices. Here, we report the effect of nitridation of HfO2 surface on the physical properties of gallium nitride (GaN) films grown on HfO2 (5 nm)/p-Si(100) substrates using laser molecular beam epitaxy (LMBE) technique. The grazing incidence x-ray diffraction (GIXRD) measurements showed the prominent GaN growth along (0002) direction. It is observed that the HfO2 nitridation significantly improves the surface coverage of GaN film with larger grains of size in the range 200 ∼ 250 nm. Room temperature photoluminescence (PL) spectroscopy exhibits a sharp, intense near band-edge emission line at 3.4 eV with negligible defect-related deep bands for the GaN film grown with HfO2 nitridation. Also, the current-voltage characteristics of Au/GaN Schottky contacts show a reduced leakage current for HfO2 nitridation. Thus, the surface nitridation of HfO2 is found vital to improve the quality of GaN films for the development of GaN-on-Si technology.